Fluorine: A new element in protein design - Buer, Benjamin C (Wiley Subscription Services, Inc., A Wiley Company, 2012)
Fluorocarbons are quintessentially man-made molecules, fluorine being all but absent from biology. Perfluorinated molecules exhibit novel physicochemical properties that include extreme chemical inertness, thermal stability, and an unusual propensity for phase segregation. The question we and others have sought to answer is to what extent can these properties be engineered into proteins? Here, we review recent studies in which proteins have been designed that incorporate highly fluorinated analogs of hydrophobic amino acids with the aim of creating proteins with novel chemical and biological properties. Fluorination seems to be a general and effective strategy to enhance the stability of proteins, both soluble and membrane bound, against chemical and thermal denaturation, although retaining structure and biological activity. Most studies have focused on small proteins that can be produced by peptide synthesis as synthesis of large proteins containing specifically fluorinated residues remains challenging. However, the development of various biosynthetic methods for introducing noncanonical amino acids into proteins promises to expand the utility of fluorinated amino acids in protein design.